Chapter Piattaforme prodotto - Romano, Antonello (Strumenti per la didattica e la ricerca, 2022)
The chapter highlights the geographies of some 'product platforms' such as Amazon, Just Eat, Netflix, Strava, also emphasizing the geoprivacy's issues.